2019
DOI: 10.1021/acsomega.8b02657
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Main Regime Transition with Variations of Gas and Liquid Phases in a Bubble Column

Abstract: Industrial bubble columns mainly operate in a heterogeneous flow regime and identifying transition from homogeneous to heterogeneous flow is important. This work addresses the determination of flow regimes with gas–liquid systems in a bubble column. Various parameters of gas holdup, volumetric mass transfer coefficient, drift flux, and pressure standard deviations were investigated to precisely determine the superficial gas velocity at the transition regime. For a column aspect ratio ( H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…Note that the main transition velocity identified in Fig. 2a is very close to the prediction of Im et al (0.048 m s −1 ) 26. Based on simulations, Wang et al 33 have shown that the transition velocity for an air‐water system is 0.04 m s −1 .…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Note that the main transition velocity identified in Fig. 2a is very close to the prediction of Im et al (0.048 m s −1 ) 26. Based on simulations, Wang et al 33 have shown that the transition velocity for an air‐water system is 0.04 m s −1 .…”
Section: Resultssupporting
confidence: 84%
“…They used a ring sparger with six legs (star-like cross). It is noteworthy that the second transition velocity U trans-2 is very close to the prediction of another correlation (0.048 m s -1 ) [26].…”
Section: Superficial Gas Velocity [M/s]supporting
confidence: 85%
See 2 more Smart Citations
“…The development of the gas–liquid two-phase flow has been an important research for many years. In the earlier periods, studies of two-phase flow in the vertical pipe were concentrated on the partition of different flow patterns by experiments, and then researchers obtained several steady-state models about pressure, density, and liquid holdup along the pipe. Later on, some researchers proposed different flow patterns, new flow pattern transition criteria, and new steady-state models to predict liquid holdup and pressure drop, and they conducted experiments to validate these models. …”
Section: Introductionmentioning
confidence: 99%